Tectonothermal Evolution of the Broadly Rifted Zone, Ethiopian Rift. Issue 3 (27th March 2019) - Boone, S. C.; Balestrieri, M.‐L.; Kohn, B. P.; Corti, G.; Gleadow, A. J. W.; Seiler, C.
Abstract: The Broadly Rifted Zone (BRZ) of southern Ethiopia is a long‐lived and structurally complex segment of the East African Rift System. However, due to poor surface exposure of early synrift strata and a dearth of subsurface data, the evolution of the BRZ remains poorly understood. We present new apatite (U‐Th‐Sm)/He and augmented apatite fission track low‐temperature thermochronology data from the Beto and Galana basin boundary fault systems to constrain the tectonothermal evolution of the western and eastern BRZ, respectively. Time‐temperature reconstructions suggest that East African Rift System‐related extension began concurrently across the BRZ in the early Miocene (20–17 Ma), at least 6 Myr prior to faulting in the Main Ethiopian Rift further north. Increased time‐temperature resolution provided by multithermochronometer analyses reveals contrasting along‐strike spatiotemporal variations in Beto and Galana margin cooling histories, which appear to mirror the disparate structural geometries of their basin‐bounding normal fault arrays. Longitudinal contrasts in basin architecture and rift‐related cooling histories across the BRZ may reflect the region's heterogeneous distribution of preexisting basement fabrics, namely, the presence of a previously reported N‐NNE trending Neoproterozoic suture zone beneath the eastern BRZ. Its influence may explain both the development of long, curvilinear faults and the gradual basinward migration of strain exhibited by the easternmost BRZ, absent further west. The anomalous evolution of the BRZ compared to the greater Ethiopian Rift, both in its earlier onset and its wider deformation zone, likely results from its inheritance of preattenuated lithosphere, thermomechanically modified by earlier Cretaceous‐Paleogene Anza‐South Sudan rifting and/or Eocene plume impingement. Key Points: Apatite (U‐Th‐Sm)/He and augmented fission track data constrain early Miocene onset of rift‐related cooling in Beto and Galana basin margins Contrasting along‐strike cooling histories of Beto and Galana margins appear to reflect disparate structural geometries of their basin‐bounding fault arrays Longitudinal contrasts in structural evolution of Broadly Rifted Zone may result from east‐west differences in preexisting lithospheric heterogeneities